Nazis, Islamists, and the making of the modern Middle East - Rubin, Barry M. 1950-2014 (Yale University Press, 2014)
"During the 1930s and 1940s, a unique and lasting political alliance was forged among Third Reich leaders, Arab nationalists, and Muslim religious authorities. From this relationship sprang a series of dramatic events that, despite their profound impact on the course of World War II, remained secret until now. In this groundbreaking book, esteemed Middle East scholars Barry Rubin and Wolfgang G. Schwanitz uncover for the first time the complete story of this dangerous alliance and explore its continuing impact on Arab politics in the twenty-first century. Rubin and Schwanitz reveal, for example, the full scope of Palestinian leader Amin al-Husaini's support of Hitler's genocidal plans against European and Middle Eastern Jews. In addition, they expose the extent of Germany's long-term promotion of Islamism and jihad. Drawing on unprecedented research in European, American, and Middle East archives, many recently opened and never before written about, the authors offer new insight on the intertwined development of Nazism and Islamism and its impact on the modern Middle East"--